2004
DOI: 10.1093/ajcn/80.2.284
|View full text |Cite|
|
Sign up to set email alerts
|

Postprandial lipid and carbohydrate responses after the ingestion of a casein-enriched mixed meal

Abstract: Casein added to a fatty meal lowers free fatty acids markedly in the postprandial and postabsorption phases, probably via its insulinotropic activity. Postprandial lipemia is also moderately reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
7
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 37 publications
4
50
7
4
Order By: Relevance
“…Although the amounts of carbohydrate (1 g/kg) and fat (0.38 g/kg) in the cookie used in the present study are similar to those in the glucose (1 g/kg)1OFTT cream (0.35 g/kg as fat) used in our earlier study (7), the cookie also contains a small amount of protein derived from butter and egg (0.11 g/kg). It was reported that postprandial lipidemia was reduced when protein (50 g sodium caseinate) was added to fat food (14); however, the rise of TG and RLP-TG in the present study was comparable to that observed in our previous study (7). This may be because the amount of protein administered in the present study was small.…”
Section: Discussioncontrasting
confidence: 54%
“…Although the amounts of carbohydrate (1 g/kg) and fat (0.38 g/kg) in the cookie used in the present study are similar to those in the glucose (1 g/kg)1OFTT cream (0.35 g/kg as fat) used in our earlier study (7), the cookie also contains a small amount of protein derived from butter and egg (0.11 g/kg). It was reported that postprandial lipidemia was reduced when protein (50 g sodium caseinate) was added to fat food (14); however, the rise of TG and RLP-TG in the present study was comparable to that observed in our previous study (7). This may be because the amount of protein administered in the present study was small.…”
Section: Discussioncontrasting
confidence: 54%
“…14,15 Although, the milk protein casein per se did not modulate the postprandial triglyceride response in T2DM. 14 However, when whey protein, another milk protein, was added to a fat-rich meal it acutely reduces the postprandial triglyceride response in T2DM subjects compared with casein, cod and gluten.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, it has been demonstrated that the addition of refined carbohydrates to a fat-rich meal increases PPL in T2DM (Brader et al, 2010). However, this observation could not be demonstrated in healthy subjects (Westphal et al, 2004;Lairon et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the unfavorable effect of carbohydrate on PPL seen in T2DM can be reduced by adding casein to the meal (Westphal et al, 2004;Brader et al, 2010). However, casein added to a fat-rich meal without carbohydrate did not affect PPL compared with a fat-rich meal per se in T2DM (Brader et al, 2010).…”
Section: Introductionmentioning
confidence: 96%